THE SAPARAN RITUAL IN CANDIREJO TOURISM VILLAGE - Rina Jatmikowati (Conscientia, 2020)
Saparan is a ritual which is held annualy in every Safar month. Saparan ritual is celebrated in many areas in Central Java. One of the villages that celebrate this ritual is Candirejo village, in Borobudur Sub-District. In this final paper, the writer is interested in writing about the process of the ritual, which includes the time, the place, the doers, the sequence of the procession, the myth, the offerings and its meaning, the function and the purpose of the ritual. To find out about the details of the ritual, the writer did both field research and library research. As the result, the writer finds that Saparan ritual in Candirejo village usually lasts in 3 days. Many activities are carried out during the Saparan ritual celebration, such as: cleaning the village together, sedekahan, kenduri, tumpengan, pengajian, gebyar rebana, traditional dance performanced like Jathilan, Ndayak’an and Pentul-Tembem dance, and the ritual is closed by the puppet show. Every activity in the Saparan ritual is always accompanied with the offerings that consist of some foods and other things as symbols that describe the relationship between humans and God. The purposes of the Saparan ritual are a way to refuse all kinds of disaster and a way to thank God for having given them the harvest and prosperity. Besides, the functions of the ritual are as the effort to keep the tradition, introduce it to the young generation and as an effort to keep the togetherness of all the villagers in Candirejo village. By this paper, the writer hopes that the readers can get more additional information about the culture heritage in Indonesia, especially about Saparan ritual in Candirejo village. Then hopefully, they will be able to appreciate the traditional cultures as a heritage of Indonesia.